2014
DOI: 10.1590/0103-8478cr20131154
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cyclic water stress on growth, physiological responses and yield of rice (Oryza sativa L.) grown in tropical environment

Abstract: [5, 10, 15, 20, 25 and 30

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 12 publications
(9 reference statements)
3
24
0
1
Order By: Relevance
“…GY, 1000 GW and biomass were also decreased at 70 and 50 % FC. Zain et al (2014) reported that GY, biomass, filled spikelet, 1000 GW and PH were reduced under increased duration of drought stress intervals. Similar results for decline in GY and plant morphology were also reported by Zulkarnain et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…GY, 1000 GW and biomass were also decreased at 70 and 50 % FC. Zain et al (2014) reported that GY, biomass, filled spikelet, 1000 GW and PH were reduced under increased duration of drought stress intervals. Similar results for decline in GY and plant morphology were also reported by Zulkarnain et al (2009).…”
Section: Resultsmentioning
confidence: 99%
“…Zain et al (2014) compararam o desempenho de uma cultivar de arroz própria para o cultivo irrigado por inundação, nos ambientes inundado, saturado e aeróbico com deficit hídrico (sem irrigação por períodos de 5, 10, 15, 20, 25 e 30 dias). Os autores observaram que a produtividade foi a mesma nos tratamentos irrigados por inundação e na condição de solo saturado, mas observaram queda de 15% na produtividade, no cultivo com cinco dias sem irrigação, e superior a 90%, nos cultivos com mais 20 dias de suspenção da irrigação.…”
Section: Resultsunclassified
“…According to Blum (2009), since biomass production is tightly linked to transpiration, breeding for maximized soil moisture capture for transpiration is the most important target for yield improvement under water deficit. Zain et al (2014) found that 15-day water deficit cycle reduced rice transpiration rate by 42% and, as it has a positive correlation with net photosynthesis rate, reduced grain yield.…”
Section: Genotypementioning
confidence: 93%